THE CORRELATION BETWEEN PROINSULIN/ INSULIN RATIO AND ADIPONECTIN RECEPTOR LEVEL AFTER GIVING THE PUGUNTANO LEAF EXTRACT (Curanga fel-terrae Merr.) IN TYPE 2 DIABETES WISTAR RAT - Farhan, Santi Syafril & Dharma Lindarto (International Journal of Research Science and Management, 2019)
Introduction: Diabetes mellitus (DM) is a chronic condition characterized by high blood glucose concentration resulting from insufficient insulin production and/ or ineffective insulin action. Proinsulin was synthesized and secreted as a insulin precursor and marker predictor of type 2 DM. Adiponectin has a contributory role in insulin sensitivity through decrease of hepatic gluconeogenesis and increased glucose transport in muscles.